Жанрова репрезентація сатиричної публіцистики: уточнення наукових підходів - Зикун, Наталія Іванівна (Київський національний університет ім.Тараса Шевченка, 2015)
Метою статті є з’ясування особливостей і ролі сатиричних жанрів публіцистики; дослідження впливу на їхній характер зображальних текстів, наділених особливою образністю й публіцистичністю. Методи. Використовувалися методи аналізу – для виокремлення із системи журналістських жанрів підгрупи сатиричних; синтезу, що забезпечив трактування публіцистичних жанрів як єдиного цілого; спостереження (за явищами й жанровими формами в сатиричному дискурсі) й описування його результатів. Систематизування даних здійснювалося із застосуванням методу класифікації, тобто групування об’єктів за певними ознаками. Головні результати. Обґрунтовується доцільність виокремлення сатиричних жанрів на підставі форми художнього відображення дійсності, принципів сатиричної типізації та специфіки сатиричного образу; своєрідного предмета відображення; особливої поетики наративу. Висновки. Доводиться необхідність уточнення конфігурації системи журналістських жанрів, яка може бути представлена чотирма групами: інформаційною, аналітичною, художньо-публіцистичною та сатиричною. Значення. Дослідження сприятиме уточненню розуміння поняття «сатиричний жанр», визначенню місця й специфіки сатиричних жанрів у загальній жанрології журналістики.

Main objectives of the study include the clarification of peculiarities of satiric genres of publicism, determination of their place in the system of journalistic genres; research of their influence on the general nature of the system of satiric genres of graphic texts provided with special vividness and publicism. Methodology. The following methods of research were used by the author: analysis that consisted in the selection of sub-group of humorous and satiric genres from the system of journalistic ones; synthesis that provided the interpretation of modern publicism genres as a single unit due to the presence of common features and geneticallyfunctional interrelations between them as well as the combination of particular features of genres of the mentioned sub-group in the complex of genre-constituting factors. The material for the study was received due to the empirical methods of supervision (over the phenomena and facts in satiric discourse and genre forms) and description of its results. The data systematization was done by the means of classification method that is by the means of grouping the research objects based on certain signs. Main findings. The expediency of selection of satiric genres (both text and graphic) into a separate group is proved on the basis of the form of artistic reflection of reality, the principles of satiric typification and specific of satiric character; original article of reflection; special poetics of the narrative. Conclusions. The author proves the necessity of clarification of the system of journalistic genres that can be presented by the four groups: informative, analytical, literary publicistic and satiric. The latter contains text and graphic satiric genre constructs. In turn text satiric genres can be informative (satiric note, satiric reporting, satiric interview), analytical (satiric articles, letters, correspondences, comments) and literary publicistic (feuilleton, pamphlet). Significance. The study will assist the clarification of understanding the concept of “satiric genre”, determination both the place and specific of satiric genres in the general genrelogy of journalism.
Keywords: жанр; сатиричний жанр; текстові сатиричні жанри; зображальні сатиричні жанри; genre; satiric genre; text satiric genres; graphic satiric genres